Raman spectroscopy of biological tissue for application in optical diagnosis of malignancy - Stone, Nicholas (Department of Environmental and Ordnance Systems, 2009)
The utilisation of near-infraredR aman spectroscopyfo r the discrimination of cancersa nd pre-cancers from normal tissue in the acro-digestive tract has been evaluated. A commercially available Raman microspectrometehr as been modified to provide optimum throughput, sensitivity and fluorescence suppression for epithelial tissue measurements. Laser excitation at 830nmw as demonstratedto be optimum. High quality (SN ratio 15-20) NIR-Raman spectrah ave been acquired from oesophageaal nd laryngeal tissues in time scales under 30 seconds. Pathological groupings covering the full range of normal and neoplastic tissues in the organs of interest have been studied. Both fresh (snap frozen) and formalin fixed tissue samples were investigated,f irstly to indicate whether tissue-typesc an be distinguishedi n vivo and secondlyt o demonstrateth e use of Raman spectroscopya s a tool for classificationi n the pathology lab. Results using multivariate statistical techniques to distinguish between spectra from specimens exhibiting different tissue pathologies have been extremely promising. Crossvalidation of the spectral predictive models has shown that three groups of larynx tissue can be separated with sensitivities and specificities of between 86 and 90% and 87 and 95% respectively. Oesophageal prediction models have demonstrated sensitivities and specificities of 84 to 97% and 93 to 98% respectively for a three-group consensus model and 73 to 100% and 92 to 100% for an eight-groupc onsensusm odel. Epithelial tissues including stomach, tonsil, endometrium, bladder and prostate have been studiedt o identify further tissuesw hereR amans pectroscopym ay be employedf or detection of disease.S pectraw ere similar to those obtainedf rom oesophagusa nd larynx, although sufficiently different for distinct discriminant models to be required. This work has demonstratedth e genericn atureo f Ramans pectroscopyfo r the detectiona nd classification of cancersa nd pre-cancerousle sionsi n many tissues.T he evidencep rovided by this study indicatest hat utilisation of Ramans pectroscopyfo r non-invasived etectiona nd classification of diseaseis a distinct possibility. Potentiald ifficulties in the transferabilityf rom in vitro to in vivo have been evaluated and no significant barriers have been observed. However, further in vivo probe development and optimisation will be required before 'optical biopsy' with Ramans pectroscopyc anb ecomea reality.
Keywords: Raman spectroscopy; Pathology; Medical screening; Evidence-based medicine; Optical coherence tomography